STRATEGI MENINGKATKAN KUALITAS GURU DI ERA GLOBAL - Nur Isnaeni; Muhammad Wahyudi (Jurnal At-Tabayyun, 2022)
Teacher is a person who imparts knowladge to students. The teacher’s responsibility is not only at school. The guidance that the teacher must provide is not only in groups, but also individually. This inevitably requires teachers to always pay attention tho the attitudes, behavior, and actions of their, not only in the school environment but also outside the school. To achieve maximum educational goals, it is necessary to have teachers who have good quality and profesionalism. Teacher profesionalism can be shown through his responsibility in carrying out all his services. Profesional teachers have personal, social intellectual, moral and spiritual responsibilities. Teachers are also expected to have a spirit of profesionalism, namely a mental attitude that always encourages them to realize themselves as professiobal officers.